Improved Simulation of the Polar Atmospheric Boundary Layer by Accounting for Aerodynamic Roughness in the Parameterization of Surface Scalar Exchange Over Sea Ice. (9th March 2023) - Elvidge, A. D.; Renfrew, I. A.; Edwards, J. M.; Brooks, I. M.; Srivastava, P.; Weiss, A. I.
Abstract: A new, simple parameterization scheme for scalar (heat and moisture) exchange over sea ice and the marginal ice zone is tested in a numerical weather and climate prediction model. This new " Blended A87 " scheme accounts for the influence of aerodynamic roughness on the relationship between momentum and scalar exchange over consolidated sea ice, in line with long‐standing theory and recent field observations, and in contrast to the crude schemes currently operational in most models. Using aircraft observations and Met Office Unified Model simulations of cold‐air outbreak (CAO) conditions over aerodynamically rough sea ice, we demonstrate striking improvements in model performance when the Blended A87 scheme replaces the model's operational treatment for surface scalar exchange, provided that the aerodynamic roughness over consolidated ice is appropriately prescribed. The mean biases in surface sensible heat flux, surface latent heat flux, near‐surface air temperature, and surface temperature reduce from 25 to 11 W m −2, 22 to 12 W m −2, 0.8 to 0.0 K, and 1.4 to 0.8 K, respectively. We demonstrate that such impacts on surface exchange over sea ice can have a marked impact on the evolution of the atmospheric boundary layer across hundreds of kilometres downwind of the sea ice during CAO conditions in the model. Our results highlight the importance of spatiotemporal variability in the topography of consolidated sea ice for both momentum and scalar exchange over sea ice; accounting for which remains a key challenge for modeling polar weather and climate. Plain Language Summary: A new algorithm for the turbulent exchange of heat and moisture between the atmosphere and the ice‐covered oceans of the polar regions is tested in a state‐of‐the‐art weather and climate model. The algorithm is applicable both over consolidated sea ice and in regions characterized by a mixture of open seawater and ice. It accounts for the influence of aerodynamic roughness (a function of wind speed and the fine‐scale topographic roughness of the surface), in line with long‐standing theory and recent field observations, and in contrast to the crude schemes currently operational in most models. Using low‐altitude aircraft observations from over the Arctic Ocean and Nordic Seas, we demonstrate striking improvements in model performance when the new algorithm replaces the model's operational treatment for surface scalar exchange, provided that the aerodynamic roughness over consolidated ice is appropriately prescribed. The mean biases in surface sensible heat flux, surface latent heat flux, near‐surface air temperature and surface temperature reduce from 25 to 11 W m −2, 22 to 12 W m −2, 0.8 to 0.0 K, and 1.4 to 0.8 K, respectively. We demonstrate that such impacts on surface exchange over sea ice can have a significant impact on model prediction of high‐latitude weather. Key Points: The model reproduction of scalar fluxes over sea ice is improved with a new parameterization that accounts for aerodynamic roughness The properties and structure of the polar atmospheric boundary layer are sensitive to the implementation of this new parameterization The benefit of the parameterization accounting for aerodynamic roughness hinges on the appropriate prescription of sea‐ice topography